Identifying Contractorsâ Planned Quality Costs in Indonesian Construction Projects - Puti F. Marzuki; M. Wisridani (Institute for Research and Community Services, Institut Teknologi Bandung, 2014)
In a very competitive construction industry, quality costs have to be measured to be able to identify potential quality problem areas and to focus attention on work output improvement opportunities. The awareness of contractors on the importance of quality costs could be reflected in the extent of their quality costs planning. This paper presents an identification of planned quality costs in three construction projects executed by two large Indonesian contractors, a state-owned company and a private company in Jakarta. The objective is to enable the contractors to elaborate their quality costs planning and thereby improve their work output based on the findi ngs. Quality costs are first grouped into three categories: prevention, appraisal, and failure costs. Based on the works of previous researchers, a list of quality management activities that should be covered in each quality costs category is then created. The contractors' planned quality costs data for each category are identified and collected through interviews and questionnaire surveys that refer to the list. Quality costs are expressed as a percentage of contract value. It is revealed that although large contractors already have certain knowledge on quality costs in construction projects, these costs are not planned in a structured way through an analysis of systematic quality costs records. Through cost categorization it is also shown that higher prevention and appraisal costs lead to lower failure costs. It is then concluded that a lot of work is still to be done by the contractors to set up a quality costs recording system which can serve as a basis for their quality improvement planning.